2018
DOI: 10.1159/000491688
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>ANTXR1</i></b> Intronic Variants Are Associated with Fetal Hemoglobin in the Arab-Indian Haplotype of Sickle Cell Disease

Abstract: Disease severity of sickle cell anemia is highly variable, and it is commonly accepted that fetal hemoglobin (HbF) levels play a major role as an ameliorating factor. Investigation of genetic variants have identified several genes to be the principal influencers of HbF regulation. Here, we further elucidated the association of rs4527238 and rs35685045 of ANTXR1 genes in the context of HbF level variance in sickle cell anemia patients of the Arab-Indian haplotype. Samples from 630 sickle cell anemia patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…Anthrax toxin receptor 1 (ANTXR1), a type I transmembrane protein, also known as tumor endothelial marker 8 (TEM8), was initially identified because of its overexpression in the endothelial cells (ECs) that is associated with human colorectal cancer [ 9 12 ] Previous studies had not shown an association between ANTXR1 and hematological phenotypes until the recent finding that a single nucleotide polymorphism (SNP, rs4527238, T>C) in intron 9 of the ANTXR1 gene was associated with the regulation of HbF levels in Saudi patients with SCD [ 13 ]. Several other studies and our research reconfirmed that the genotypes of two SNPs (rs4527238 and rs35685045) in the ANTXR1 gene were associated with HbF levels in individuals with β -thalassemia minor and sickle cell anemia [ 14 ]. These findings suggest that ANTXR1 is involved in the regulation of γ -globin gene expression.…”
Section: Introductionsupporting
confidence: 76%
“…Anthrax toxin receptor 1 (ANTXR1), a type I transmembrane protein, also known as tumor endothelial marker 8 (TEM8), was initially identified because of its overexpression in the endothelial cells (ECs) that is associated with human colorectal cancer [ 9 12 ] Previous studies had not shown an association between ANTXR1 and hematological phenotypes until the recent finding that a single nucleotide polymorphism (SNP, rs4527238, T>C) in intron 9 of the ANTXR1 gene was associated with the regulation of HbF levels in Saudi patients with SCD [ 13 ]. Several other studies and our research reconfirmed that the genotypes of two SNPs (rs4527238 and rs35685045) in the ANTXR1 gene were associated with HbF levels in individuals with β -thalassemia minor and sickle cell anemia [ 14 ]. These findings suggest that ANTXR1 is involved in the regulation of γ -globin gene expression.…”
Section: Introductionsupporting
confidence: 76%
“…El‐Hazmi et al described the genotypes and phenotypes of SCD in the Arab population in 2011 8 . Since then, there have been many new studies describing variants of SCD genotypes and phenotypes, and with the emerging era of gene therapy for SCD, it is essential to compile the current evidence, especially in the last 5 years 22‐44 . We will pool all data describing the genotypic and phenotypic variants of SCD in the Arab population to date in a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…In the last issue of Acta Haematologica, Al-Ali et al [7] replicated the original observations in 630 new AI haplotype homozygotes and used different methods of genotyping and analysis, thereby lending further credence to this association. Unfortunately, association provides no information about causation.…”
mentioning
confidence: 94%